Misdiagnosis Diagnosis of Pneumocystis Pneumonia as Chemical Pneumonitis - Zhou M; Jiang X; Kong Y; Liu X (Infection and Drug Resistance, 2024)
Mi Zhou,* Xinyu Jiang,* Yulin Kong, Xiaolin Liu Department of Occupational Disease, The Fifth People’s Hospital of Suzhou, Jiangsu, 215100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaolin Liu, Department of Occupational Disease, The Fifth People’s Hospital of Suzhou, No. 10 of Guangqian Road, Xiangcheng District, Suzhou, Jiangsu, 215100, People’s Republic of China, Tel +86 13862098055, Email xiaolinliulxl@126.comBackground: Auxiliaries, a mixed chemicals, for printing and dyeing characterized by their diverse range and complex chemical compositions are commonly utilized in the textile industry. These chemicals can lead to environmental contamination and pose health risks to humans.Case Description: A 29-year-old man who worked in a printing and dyeing factory in Suzhou, China, reported having tightness in his chest and coughing. Despite seeking medical treatment at several hospitals, the initial diagnosis remained elusive. High-resolution chest CT scans showed multifocal lesions in both lungs. The patient had no significant medical history, and the respiratory symptoms only surfaced after exposure to dyeing auxiliaries. Physicians initially suspected chemical pneumonitis due to occupational exposure. However, a subsequent evaluation at a hospital specializing in occupational diseases led to a diagnosis of AIDS and pneumocystis pneumonia.Conclusion: This case underscores the importance of comprehensive clinical diagnosis to avoid biases and reduce the incidence of misdiagnosis.Keywords: chemical pneumonitis, high-resolution CT, misdiagnosis, pneumocystis pneumonia, printing and dyeing auxiliaries